2002
DOI: 10.1002/ptr.1063
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties of Indian medicinal plants

Abstract: The antioxidant properties of methanol extracts of 12 Indian medicinal plants, traditionally used in disease areas that probably involve free radical mechanisms, were evaluated by two methods, namely the DPPH (1,1-diphenyl-2-picryl hydrazyl) test and the lipid peroxidation assay. In the latter assay, seven of these extracts showed 90% or more activity compared with the standard, vitamin E and hence were studied in detail after the removal of interfering pigments. The selective pigment removal from the extracts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 9 publications
2
33
0
Order By: Relevance
“…Moreover, this could be associated with a down regulation in LDL receptors by the cholesterol in the diet, which could also explain the elevation of serum LDL cholesterol levels or non-HDL levels either by changing hepatic LDL receptor activity, the LDL production rate or both (Jadhav and Bhutani, 2002) In the present study rats fed with AD showed significant increase in TC, TG and non-HDL, TC: HDL and AI values (Table 2) confirming that cholesterol feeding induced hypercholesteremia experimentally. When compared to AD treated group, treatment of experimentally induced hyperlipidemic rats with MECF and AECF at the dose of 400 mg/kg showed highly significant decrease of non-HDL, TC: HDL and AI (p < 0.001) TC showed significant of (p < 0.05) whereas TG does not showed significant, with significant increase in HDL (p < 0.001) than the lower dose of 200 mg/kg.…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, this could be associated with a down regulation in LDL receptors by the cholesterol in the diet, which could also explain the elevation of serum LDL cholesterol levels or non-HDL levels either by changing hepatic LDL receptor activity, the LDL production rate or both (Jadhav and Bhutani, 2002) In the present study rats fed with AD showed significant increase in TC, TG and non-HDL, TC: HDL and AI values (Table 2) confirming that cholesterol feeding induced hypercholesteremia experimentally. When compared to AD treated group, treatment of experimentally induced hyperlipidemic rats with MECF and AECF at the dose of 400 mg/kg showed highly significant decrease of non-HDL, TC: HDL and AI (p < 0.001) TC showed significant of (p < 0.05) whereas TG does not showed significant, with significant increase in HDL (p < 0.001) than the lower dose of 200 mg/kg.…”
Section: Discussionsupporting
confidence: 75%
“…The experiment was repeated three times. The difference in the absorbances between the test and the control were calculated and expressed as the percentage scavenging of DPPH radical (Jadhav & Bhutani, 2002).…”
Section: In Vitro Antioxidant Activitymentioning
confidence: 99%
“…Free radicals are harmful and cause oxidative stress which may cause very serious human diseases (Vani et al, 1997;Jadhav and Bhutani, 2002). Many natural products have been using in practice for the cure of free radicals (Kokate, 2004).…”
Section: Introductionmentioning
confidence: 99%